Thromboembolic and bleeding complications in patients with oesophageal cancer. Issue 10 (19th May 2020) - Mulder, F I; Hovenkamp, A; Laarhoven, H W M; Büller, H R; Kamphuisen, P W; Hulshof, M C C M; Berge Henegouwen, M I; Middeldorp, S; Es, N
Abstract: Background: In patients who undergo curative treatment for oesophageal cancer, risk estimates of venous thromboembolism (VTE), arterial thromboembolism and bleeding are needed to guide decisions about thromboprophylaxis. Methods: This was a single-centre, retrospective cohort study of patients with stage I–III oesophageal cancer who received neoadjuvant chemoradiation followed by oesophagectomy. The outcomes VTE, arterial thromboembolism, major bleeding, clinically relevant non-major bleeding and mortality were analysed for four consecutive cancer treatment stages (from diagnosis to neoadjuvant chemoradiotherapy, during neoadjuvant treatment, 30-day postoperative period, and up to 6 months after postoperative period). Results: Some 511 patients were included. The 2-year survival rate was 67·3 (95 per cent c.i. 63·2 to 71·7) per cent. During the 2-year follow-up, 50 patients (9·8 per cent) developed VTE, 20 (3·9 per cent) arterial thromboembolism, 21 (4·1 per cent) major bleeding and 30 (5·9 per cent) clinically relevant non-major bleeding. The risk of these events was substantial at all treatment stages. Despite 30-day postoperative thromboprophylaxis, 17 patients (3·3 per cent) developed VTE after surgery. Patients with VTE had worse survival (time-varying hazard ratio 1·81, 95 per cent c.i. 1·25 to 2·64). Most bleeding events occurred around the time of medical intervention, and approximately one-half during concomitant use of prophylactic or therapeutic anticoagulation. Conclusion: Patients with oesophageal cancer undergoing neoadjuvant chemoradiotherapy and surgery are at substantial risk of thromboembolic and bleeding events throughout all stages of treatment. Survival is worse in patients with thromboembolic events during follow-up. Graphical Abstract: A total of 511 patients who underwent curative chemoradiotherapy and subsequent tumour resection for oesophageal cancer were reviewed retrospectively for bleeding events and arterial or venous thromboembolism (VTE). During the 2-year follow-up, 50 patients (9·8 per cent) developed VTE, 20 (3·9 per cent) arterial thromboembolism, 21 (4·1 per cent) major bleeding and 30 (5·9 per cent) clinically relevant non-major bleeding. Perhaps inevitable